The effect of COVID-19 lockdown on the epidemiology of maxillofacial trauma at tertiary health facilities in Pretoria - Khan, Nazia; Madiba, Thomas Khomotjo; Xoki, Buntu; Mjoli, Wenzile; Nevhutalu, Thendo (South African Dental Journal, 2023)
Background: COVID-19 restrictions have reduced the number of consultations of patients including Maxillo-facial trauma patients. Aim: To analyse and compare the epidemiology of maxillofacial trauma during four months of the lockdown period and compare it with the same months from the previous year (2019 and 2020). Materials and Method: A retrospective record-based study was conducted with data drawn from all maxillofacial trauma patients who presented in the maxillofacial and oral surgery unit, of the University of Pretoria (UP) and Steve Biko Academic Hospital (SBAH) from April to July of 2019 and April to July of 2020. Data collected included age, gender, aetiology of injury, site of injury, severity and extent of injury, fracture pattern and site, waiting period for treatment and month of injury. Chi-square test was used to evaluate the association between variables. The level of significant was set at p ≤ 0.05. Results: A total of 197 patients were seen in the two institutions with maxillofacial injuries for the years 2019 and 2020 with ages ranging from 1 to 81 years and a mean of 36.24. Most patients were males 167(85%). Many patients were seen in 2019 at 139(71%). There was no association between the fracture site and the aetiology. The mandible was significantly the most common site of injury and more conservative treatment was done as compared to other forms of treatment (p < 0.05). Conclusion: More Maxillofacial cases were seen in 2019 than in 2020 with more males as compared to females. The majority of injuries were assaults followed by motor vehicle accidents (MVA). The mandible was the common site of injury. More conservative treatment was done compared to other forms of treatment.